Flexible diatomite decorative composite board and preparation method thereof

CN118544617BActive Publication Date: 2026-10-27山东凯大新型材料科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410660249.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-27
Publication Date
2026-10-27
Estimated Expiration
2044-05-27

AI Technical Summary

Technical Problem

在实际应用中,这种脆性导致硅藻土装饰板容易在物理冲击下破裂,特别是在需要柔性处理或弯曲安装的场景中,其应用受到严重限制

Benefits of technology

本发明实施例提供的技术方案带来的有益效果是:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a kind of flexible diatomite decorative composite board and preparation method thereof, it is related to decorative composite board technical field, technical scheme is to be dissolved in deionized water with polyvinyl alcohol (PVA) particle, heating and stirring to completely dissolve;PVA solution, modified diatomite, polyurethane fiber, flame retardant, dispersing agent, mildew preventive agent are uniformly mixed initially using low-speed stirring, and pre-mixed material is obtained;Composite binder is gradually added to the pre-mixed material, continue to be stirred at low speed until the binder is completely uniformly distributed, and a mixture is obtained;The mixture is formed in mould, and the vibration table is vibrated to remove bubbles, and after natural drying at room temperature, heat pressing solidification is carried out;Material is sanded, and encapsulation is carried out after using epoxy resin coating uniform coating.The application is applied by modified diatomite and polyurethane fiber, significantly improves the elasticity, flexibility and interface bonding force of composite material, enhances the structural stability, and optimizes the wear resistance and environmental adaptability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of decorative composite panel technology, and in particular to a flexible diatomaceous earth decorative composite panel and its preparation method. Background Technology

[0002] With advancements in building materials technology, the market demand for environmentally friendly and highly functional decorative materials continues to grow. Diatomaceous earth, due to its excellent moisture-regulating and environmentally friendly properties, has been widely used in interior decoration. While traditional diatomaceous earth decorative panels are environmentally friendly, their flexibility and durability often fail to meet the diverse needs of modern architecture, limiting their application scope.

[0003] Traditional diatomaceous earth decorative panels possess high hardness, which, while ensuring durability to some extent, also introduces significant brittleness. In practical applications, this brittleness makes diatomaceous earth decorative panels prone to cracking under physical impact, severely limiting their application, especially in scenarios requiring flexible handling or bending installation. During the preparation of composite materials, the bonding of diatomaceous earth with other polymer materials (such as polyurethane) is often less than ideal. Due to the natural surface properties and chemical stability of diatomaceous earth, it is difficult to form strong chemical or physical bonds with the polymer matrix, thus affecting the mechanical strength and long-term durability of the final composite material. Furthermore, while the porous structure of diatomaceous earth contributes to its hygroscopicity, it can also become a weakness due to uneven force distribution within the composite material. Despite diatomaceous earth's excellent hygroscopic and environmentally friendly properties, its processing difficulties are a significant technical challenge. The high fineness and hygroscopic nature of diatomaceous earth powder lead to agglomeration during processing, making it difficult to disperse evenly within the polymer matrix. This not only increases the complexity of the production process but may also affect the uniformity and surface smoothness of the composite board.

[0004] In view of the shortcomings of existing technologies, this invention proposes to enhance the flexibility and polymer compatibility of diatomaceous earth by using modifiers and specific preparation processes, thereby solving the problems of brittleness and insufficient interfacial bonding strength of diatomaceous earth in practical applications. This improvement aims to expand the application range of diatomaceous earth decorative panels, especially in the field of decorative materials requiring high flexibility and high durability. Through this technological innovation, the market competitiveness of diatomaceous earth composite panels can be significantly enhanced, meeting the dual requirements of modern building decoration materials for environmental protection and functionality. Summary of the Invention In order to achieve the above-mentioned objectives and address the above-mentioned technical problems: This invention provides a method for preparing a flexible diatomaceous earth decorative composite board, comprising the following steps: A1 Dissolve polyvinyl alcohol (PVA) particles in deionized water, heat and stir until completely dissolved; A2 uses low-speed stirring to initially and uniformly mix PVA solution, modified diatomaceous earth, polyurethane fiber, flame retardant, dispersant, and mildew inhibitor to obtain a premixed material; A3. Gradually add the composite adhesive to the premixed material in step A2, and continue stirring at a low speed until the adhesive is completely and uniformly distributed to obtain a mixture; A4. The mixture from step A3 is molded in a mold, vibrated to remove bubbles using a vibrating table, and then allowed to dry naturally at room temperature before being cured by hot pressing. A5 involves sanding the material obtained from A4, uniformly coating it with epoxy resin, and then encapsulating it.

[0005] Preferably, in step A1, the molecular weight of PVA is 80,000-100,000, the water solubility is 95-99%, the solution concentration is 5-15%, and the heating temperature is 80-95℃.

[0006] Preferably, in step A2, the weight ratio of PVA solution, modified diatomaceous earth, and polyurethane fiber is 4:2:1 to 6:4:3; and the stirring speed is 100-500 rpm. Preferably, the polyurethane fiber has a linear density of 2.0-2.5 dtex and an elastic modulus of 450-550 MPa.

[0007] Preferably, the modified diatomaceous earth is prepared by mixing diatomaceous earth with isocyanate at a mass of 1-3% and stirring at room temperature until homogeneous, wherein the average particle size of the diatomaceous earth is 25-35 micrometers.

[0008] Preferably, the amount of composite adhesive added in step A3 is 5-10% of the total mass, and the composite adhesive is a mixture of polyurethane adhesive and vinyltrimethoxysilane, wherein vinyltrimethoxysilane accounts for 1-5% of the mass of polyurethane adhesive.

[0009] Preferably, in step A4, the curing temperature is 55-65℃, the pressure is 4-6 MPa, and the hot-pressing time is 1-3 hours.

[0010] Preferably, the vibration time in step A4 is 3-7 minutes and the frequency is 30-60 Hz.

[0011] Preferably, the epoxy resin coating thickness in step A4 is 0.3-0.7 mm.

[0012] Preferably, the decorative composite panel is prepared by the method.

[0013] This invention achieves significant technological advancements and beneficial effects through a unique combination of materials and meticulously designed process steps. First, in step A1, polyvinyl alcohol (PVA) is dissolved in deionized water and heated with stirring, laying the foundation for uniform mixing of subsequent materials. Next, in step A2, modified diatomaceous earth and polyurethane fibers are added, and low-speed stirring ensures uniform distribution of each component. Furthermore, the introduction of modified diatomaceous earth, when mixed with isocyanate, enhances its compatibility with organic polymers, improving material dispersibility and interfacial bonding.

[0014] In step A3, the bonding between diatomaceous earth and polyurethane fibers was optimized by adding a composite adhesive and continuing stirring. This composite adhesive, composed of polyurethane adhesive and vinyltrimethoxysilane, not only improved the compatibility of the two materials but also enhanced the interfacial bonding force through chemical bonding. In the subsequent step A4, the composite was molded in a mold and vibrated on a vibrating table to remove bubbles, ensuring the structural stability and uniformity of the composite board during the curing process. Finally, the sanding and epoxy resin coating in step A5 further improved the surface properties and durability of the product.

[0015] The integration of these technical strategies not only addresses the hardness and brittleness issues of diatomaceous earth decorative panels but also overcomes the challenges of insufficient interfacial bonding and processing difficulties. Overall, this invention optimizes the performance of traditional diatomaceous earth decorative panels through the principles of materials science and chemical engineering, enabling them to exhibit superior application flexibility and environmental adaptability in various environments, thus meeting the market demand for high-performance, environmentally friendly materials. The beneficial effects of the technical solution provided by the embodiments of the present invention are as follows: This invention utilizes polyurethane fiber as a key component of the composite material, significantly enhancing the elasticity and flexibility of diatomaceous earth decorative panels. Polyurethane fiber possesses a high elastic modulus (450-550 MPa), playing a role in enhancing structural stability and wear resistance within the composite material. Furthermore, the application of polyurethane fiber in the diatomaceous earth matrix effectively improves the brittleness of traditional diatomaceous earth panels, making them more suitable for applications that may be subject to physical impacts or require flexible installation.

[0016] The composite adhesive of this invention, prepared by mixing polyurethane adhesive and vinyltrimethoxysilane, solves the technical problem of insufficient interfacial adhesion between diatomaceous earth and polyurethane fibers. The composite adhesive not only improves the compatibility between the two materials but also enhances the interfacial bonding force through chemical bonding. This technological advancement ensures the stability and durability of the composite material under mechanical stress, thereby improving the overall performance and reliability of the product.

[0017] By modifying diatomaceous earth with isocyanate, this invention significantly enhances the functionality of diatomaceous earth. The modified diatomaceous earth exhibits better compatibility with polymer materials and stronger adsorption capacity, improving the internal structural consistency of the materials. This modification not only optimizes the dispersibility of diatomaceous earth and reduces agglomeration during processing, but also improves its stability and environmental adaptability in composite materials. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. Of course, the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0019] Example 1 Polyvinyl alcohol (PVA) particles with a molecular weight of 95,000 and a water solubility of 99% were dissolved in deionized water. The PVA concentration was 10%, and the solution was stirred at 90°C until completely dissolved. Diatomaceous earth was mixed with 3% isocyanate at a mass ratio and stirred at 200 rpm using a mechanical stirrer at room temperature to ensure that the isocyanate completely covered the surface of the diatomaceous earth, thereby improving its surface properties. The average particle size of the diatomaceous earth was 30 micrometers. The dissolved PVA solution was mixed with modified diatomaceous earth and polyurethane fiber in a weight ratio of 5:3:2. 0.5% polyvinyl acetate dispersant and 0.2% ZPT-10 antifungal agent were added by weight. The mixture was stirred at a low speed of 100 rpm to ensure uniform mixing of all components, forming a premixed material. The polyurethane fiber had a linear density of 2.0 dtex and an elastic modulus of 550 MPa. Add 8% of the total mass of composite adhesive to the mixture, with vinyltrimethoxysilane accounting for 2% of the polyurethane adhesive SikaBond-T55, and continue stirring at 150 rpm to ensure that the adhesive is completely and evenly distributed in the mixture. Pour the mixture into a pre-prepared mold and vibrate it on a 50 Hz vibrating table for 5 minutes to remove air bubbles. Then, allow it to air dry at room temperature for 20 hours, followed by hot pressing at 60°C and 5 MPa for 1.5 hours to achieve full curing. Use sandpaper to sand the surface to remove uneven parts. Finally, apply an epoxy resin coating with a thickness of 0.5mm evenly to the surface of the board for sealing.

[0020] Example 2 Flexible diatomaceous earth decorative composite panels were prepared using the same preparation method as in Embodiment 1, except that diatomaceous earth was mixed with 1% isocyanate at a mass ratio.

[0021] Example 3 Flexible diatomaceous earth decorative composite panels were prepared using the same preparation method as in Embodiment 1, except that the linear density of the polyurethane fibers was 2.5 dtex and the elastic modulus was 450 MPa.

[0022] Example 4 Flexible diatomaceous earth decorative composite panels were prepared using the same preparation method as in Embodiment 1, except that the weight ratio of PVA solution, modified diatomaceous earth, and polyurethane fiber was 4:2:1.

[0023] Example 5 Flexible diatomaceous earth decorative composite panels were prepared using the same preparation method as in Embodiment 1, except that the weight ratio of PVA solution, modified diatomaceous earth, and polyurethane fiber was 6:4:3.

[0024] Example 6 Flexible diatomaceous earth decorative composite panels were prepared using the same preparation method as in Embodiment 1, except that the amount of composite adhesive used was 5%.

[0025] Example 7 Flexible diatomaceous earth decorative composite panels were prepared using the same preparation method as in Embodiment 1, except that the amount of composite adhesive used was 10%.

[0026] Example 8 Flexible diatomaceous earth decorative composite panels were prepared using the same preparation method as in Embodiment 1, except that vinyltrimethoxysilane accounted for 1% of the mass of the polyurethane adhesive. Example 9 Flexible diatomaceous earth decorative composite panels were prepared using the same preparation method as in Embodiment 1, except that vinyltrimethoxysilane accounted for 5% of the mass of the polyurethane adhesive. Example 10 Flexible diatomaceous earth decorative composite panels were prepared using the same preparation method as in Embodiment 1, except that the curing temperature was 55°C, the pressure was 4 MPa, and the hot-pressing time was 1 hour.

[0027] Example 11 Flexible diatomaceous earth decorative composite panels were prepared using the same preparation method as in Embodiment 1, except that the curing temperature was 65°C, the pressure was 6 MPa, and the hot-pressing time was 3 hours.

[0028] Example 12 Polyvinyl alcohol (PVA) particles with a molecular weight of 80,000 and a water solubility of 95% were dissolved in deionized water. The PVA concentration was 5%, and the solution was stirred at 80°C until completely dissolved. Diatomaceous earth was mixed with 1% isocyanate at a mass ratio and stirred at 100 rpm using a mechanical stirrer at room temperature to ensure that the isocyanate completely covered the surface of the diatomaceous earth, thereby improving its surface properties. The average particle size of the diatomaceous earth was 25 micrometers. The dissolved PVA solution was mixed with modified diatomaceous earth and polyurethane fiber in a weight ratio of 5:3:2. 0.5% polyvinyl acetate dispersant and 0.2% ZPT-10 antifungal agent were added by weight. The mixture was stirred at a low speed of 100 rpm to ensure uniform mixing of all components, forming a premixed material. The polyurethane fiber had a linear density of 2.0 dtex and an elastic modulus of 450 MPa. Add 5% of the total mass of composite adhesive to the mixture, and vinyltrimethoxysilane accounts for 1% of the polyurethane adhesive SikaBond-T55. Continue stirring at 150 rpm to ensure that the adhesive is completely and evenly distributed in the mixture. Pour the mixture into a pre-prepared mold and vibrate it on a 30 Hz vibrating table for 3 minutes to remove air bubbles. Then, allow it to air dry at room temperature for 20 hours, followed by hot pressing at 55°C and 4 MPa for 1 hour to achieve full curing. Use sandpaper to sand the surface to remove uneven parts. Finally, apply an epoxy resin coating with a thickness of 0.3mm evenly to the surface of the board for sealing.

[0029] Example 13 Polyvinyl alcohol (PVA) particles with a molecular weight of 100,000 and a water solubility of 99% were dissolved in deionized water. The PVA concentration was 15%, and the solution was stirred at 95°C until completely dissolved. Diatomaceous earth was mixed with 1% isocyanate at a mass ratio and stirred at 500 rpm using a mechanical stirrer at room temperature to ensure that the isocyanate completely covered the surface of the diatomaceous earth, thereby improving its surface properties. The average particle size of the diatomaceous earth was 35 micrometers. The dissolved PVA solution was mixed with modified diatomaceous earth and polyurethane fiber in a weight ratio of 5:3:2. 0.5% polyvinyl acetate dispersant and 0.2% ZPT-10 antifungal agent were added by weight. The mixture was stirred at a low speed of 100 rpm to ensure uniform mixing of all components, forming a premixed material. The polyurethane fiber had a linear density of 2.5 dtex and an elastic modulus of 550 MPa. Add 10% of the total mass of the composite adhesive to the mixture, and the vinyltrimethoxysilane accounts for 5% of the polyurethane adhesive SikaBond-T55. Continue stirring at 150 rpm to ensure that the adhesive is completely and evenly distributed in the mixture. Pour the mixture into a pre-prepared mold and vibrate it on a 60 Hz vibrating table for 3 minutes to remove air bubbles. Then, allow it to air dry at room temperature for 20 hours, followed by hot pressing at 6 MPa for 3 hours at 65°C to achieve full curing. Use sandpaper to sand the surface to remove uneven parts. Finally, apply an epoxy resin coating with a thickness of 0.7mm evenly to the surface of the board for sealing.

[0030] Comparative Example 1 Diatomaceous earth decorative composite panels were prepared using the same preparation method as in Embodiment 1, except that unmodified ordinary diatomaceous earth with an average particle size of 30 micrometers was used.

[0031] Comparative Example 2 Diatomaceous earth decorative composite boards were prepared using the same preparation method as in Embodiment 1, except that bamboo fibers were used instead of polyurethane fibers in the wood fibers. The fibers were 2-5 mm long and 100-200 micrometers in diameter. The bamboo fibers were treated with alkali to remove impurities such as lignin and hemicellulose. The fibers were treated in a 3% sodium hydroxide (NaOH) solution for 1 hour, and the moisture content of the bamboo fibers was kept at 6-10% by weight.

[0032] Comparative Example 3 Diatomaceous earth decorative composite boards were prepared using the same preparation method as in Embodiment 1, except that bamboo fiber from the basalt fiber in the mineral fiber was used instead of polyurethane fiber. The fiber diameter was 25 micrometers, the elastic modulus was 85 GPa, and the tensile strength was 3 GPa.

[0033] Comparative Example 4 Diatomaceous earth decorative composite panels were prepared using the same preparation method as in Embodiment 1, except that nylon 66 fibers were used instead of polyurethane fibers. The fibers had a diameter of 30 micrometers, a length of 20 mm, a tensile strength of 600 MPa, and an elastic modulus of 3 GPa.

[0034] Comparative Example 5 Diatomaceous earth decorative composite panels were prepared using the same preparation method as in Embodiment 1, except that a single polyurethane adhesive was used without the addition of vinyltrimethoxysilane.

[0035] Comparative Example 6 Diatomaceous earth decorative composite panels were prepared using the same preparation method as in Embodiment 1, except that the mixture was molded in a mold instead of using a vibration table.

[0036] Experimental test: 1. Elasticity and flexibility test: Standard: Tested in accordance with GB / T 1449-2005 "Determining Tensile Properties of Plastics".

[0037] Test method: The composite board was subjected to tensile test using a universal testing machine. The elastic modulus and elongation at break were recorded to evaluate the elasticity and flexibility of the material.

[0038] 2. Interface bond strength test: Standard: Based on GB / T 7124-2008 "Determination of interfacial shear strength of plastic composite materials".

[0039] Test method: The bond strength between diatomaceous earth and polyurethane fiber was evaluated by shear test, thereby verifying the effect of the composite adhesive.

[0040] Table 1 Elasticity and Flexibility Tests

[0041] Note: Test temperature 23℃ The test results show that Example 1 exhibits high values ​​in both elastic modulus and elongation at break, indicating optimal performance in terms of the composite material's elasticity and flexibility. The different formulations and material modifications used in Examples 2 through 5 and the comparative examples affected the performance, but none achieved the high performance of Example 1. This suggests that the formulation and process of Example 1 are most suitable for improving the flexibility and elasticity of diatomaceous earth decorative composite panels. In the comparative experiments, especially in Comparative Examples 2, 3, and 4, the non-polyurethane fibers used exhibited poorer elastic modulus and elongation at break, further validating the unique advantages of polyurethane fibers in enhancing the elasticity and flexibility of composite materials.

[0042] Table 2 Bond Strength

[0043] Note: Test temperature 23℃ Example 1 demonstrated the optimal interfacial shear strength (7.8 MPa), a result consistent with our expectations, given its use of 3% isocyanate and a high proportion (8%) of composite binder. This design not only improved the modification effect of diatomaceous earth but also significantly enhanced the internal structure and interfacial adhesion of the material through the optimized combination of polyurethane binder and vinyltrimethoxysilane, thereby achieving high mechanical stability and durability.

[0044] Examples 2 and 7 used lower isocyanate content (1%) and higher composite adhesive content (10%), respectively, with interfacial shear strengths of 5.6 MPa and 6.3 MPa. The test results of these two examples show that although some interfacial adhesion was formed, the effect was not as good as that achieved in Example 1 using 3% isocyanate and 8% composite adhesive. This demonstrates that the amounts of isocyanate and composite adhesive need to be properly balanced; after achieving a certain level of chemical modification and adhesive strength, further increasing the proportion of composite adhesive has limited effect on performance improvement.

[0045] Examples 8 and 9 tested the effect of different chemical dosages on interfacial bonding strength by adjusting the proportion of vinyltrimethoxysilane (1% and 5%, respectively), showing results at 5.2 MPa and 6.1 MPa. This indicates that a higher proportion of vinyltrimethoxysilane does not necessarily significantly improve interfacial bonding strength, but rather requires synergistic optimization with other components.

[0046] The test results (4.7 MPa) of Example 10 show that the adjustment of low curing temperature and pressure affects the bonding strength of the material, which is consistent with our understanding of the chemical and physical cross-linking during the curing process, indicating that appropriate heat treatment is a key factor in ensuring material performance.

[0047] The test results of the comparative examples further validated the effectiveness of the materials and processes used in the examples. The interfacial shear strengths of Comparative Example 1 and Comparative Example 5 were 3.9 MPa and 4.2 MPa, respectively. These lower values ​​indicate the shortcomings of the unoptimized material combination and the lack of an effective adhesive.

[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a flexible diatomaceous earth decorative composite board, comprising the following steps: A1 Dissolve polyvinyl alcohol (PVA) particles in deionized water, heat and stir until completely dissolved; A2 involves initially mixing PVA solution, modified diatomaceous earth, polyurethane fiber, flame retardant, dispersant, and mildew inhibitor using low-speed stirring to obtain a premixed material. The modified diatomaceous earth is prepared by mixing diatomaceous earth with isocyanate at a mass of 1-3% and stirring evenly at room temperature. The average particle size of the diatomaceous earth is 25-35 micrometers. A3. Gradually add the composite adhesive to the premixed material from step A2, and continue stirring at a low speed until the composite adhesive is completely and uniformly distributed, thus obtaining a mixture. The composite adhesive is added at 5-10% of the total mass, and the composite adhesive is a mixture of polyurethane adhesive and vinyltrimethoxysilane, wherein vinyltrimethoxysilane accounts for 1-5% of the mass of polyurethane adhesive; A4. Pour the mixture from step A3 into a mold for molding, use a vibrating table to remove bubbles, and allow it to dry naturally at room temperature before hot pressing for curing. A5. The material obtained in step A4 is sanded, coated evenly with epoxy resin, and then encapsulated.

2. The method for preparing the flexible diatomaceous earth decorative composite board according to claim 1, characterized in that, In step A1, the molecular weight of PVA is 80,000-100,000, the water solubility is 95-99%, the solution concentration is 5-15%, and the heating temperature is 80-95℃.

3. The method for preparing the flexible diatomaceous earth decorative composite board according to claim 1, characterized in that, In step A2, the weight ratio of PVA solution, modified diatomaceous earth, and polyurethane fiber is 4:2:1-6:4:3; the stirring speed is 100-500 rpm.

4. The method for preparing the flexible diatomaceous earth decorative composite board according to claim 1, characterized in that, The polyurethane fiber has a linear density of 2.0-2.5 dtex and an elastic modulus of 450-550 MPa.

5. The method for preparing the flexible diatomaceous earth decorative composite board according to claim 1, characterized in that, In step A4, the curing temperature is 55-65℃, the pressure is 4-6 MPa, and the hot-pressing time is 1-3 hours.

6. The method for preparing the flexible diatomaceous earth decorative composite board according to claim 1, characterized in that, In step A4, the vibration time is 3-7 minutes and the frequency is 30-60 Hz.

7. The method for preparing the flexible diatomaceous earth decorative composite board according to claim 1, characterized in that, In step A5, the epoxy resin coating thickness is 0.3-0.7 mm.

8. A flexible diatomaceous earth decorative composite board, characterized in that, The decorative composite panel is prepared by the preparation method according to any one of claims 1-7.

Citation Information

Patent Citations

  • Algae calcium compound material, decorative panel and production method

    CN102515678A

  • Diatomite modified composite environment-friendly coating and preparation method thereof

    CN109943193A